Coastal Land Preservation: Obstacles to Effective State Action - Pool, Daniel (Columbia Journal of Environmental Law, 2019)
In recent years the preservation of coastal lands and the natural resources in and around them has become a national concern. Population pressures, changing patterns of recreation, and indus- trial growth have intensified demand for the use of shorefront areas. At the same time, the need to protect coastal plants and wildlife and the terrain which supports them has become increasingly apparent. Despite widespread federal activity affecting coastal areas, the states continue to retain primary responsibility for shorelands. And since the early 1960’s, many have acted to meet the growing threat to coastal ecology, primarily through legislation. In some cases, this has involved heavy reliance on local zoning or a virtually categorical prohibition against development in specified coastal areas. In other states, legislatures have adopted sophisticated and comprehensive programs of coastal development aimed at balancing the preservation of some areas with controlled development in others. Substantial legal challenges have been mounted against legislation of both types. First, recreational shore users have persuaded state courts to open beach areas to more extensive public use. This is likely to encourage increased usage of already strained coastal land and ecosystems with potentially disastrous consequences for the coastal environment. Second, the states face potential financial obstacles in undertaking effective coastal regulation because of judicial findings that such regulation is often a taking for which private landowners must be compensated. Any serious program of conservation must prohibit land development that leads to destructive uses of ecologically valuable resources; thus most state tidelands acts typically require permission from state environmental authorities before substantial alteration may be made in the use of protected land. However, where private property is involved, the application of such a statute in a particular case may so drastically affect the economic interests of a private landowner as to constitute a taking. This note will suggest a legal framework for the exercise of state coastal authority that will render present statutes less vulnerable to attacks of this nature. After a more detailed review of current attacks on state regulation, it will be argued that they may be blunted through a combination of zoning law and the public trust doctrine.